Kajian Aksiologi terhadap Teknologi Pendeteksi Kelainan Bawaan Pada Bayi Dalam Kandungan - Raden Ahmad Hadian Adhy Permana (Jurnal Filsafat Indonesia, 2018)
Technological devices are applications of science which developed by scientists. Technology in health or medicine now has advanced and supports health practitioners to provide services for the community. One of the used is for examination of the health of the fetus in the womb. Health or abnormalities in the fetus in the womb can be detected by early screening using technological devices and standardized methods. The application of technology or science has limits on the value beside the perceived benefits. Excesses that may arise from the application of technology is the impact of several factors, especially from users, in this case are parents who are not ready if they get offspring that have a congenital abnormality. Violations of ethics and law, in the form of abortion, can occur due to information provided by the use of such technology. Scientists or competent science practitioners need to anticipate the violation of humanitarian values according to the use technological devices which they responsible